Forecasting Penjualan Gas LPG di Toko Sembako Menggunakan Metode Fuzzy Time Series - M Yoka Fathoni; Sena Wijayanto (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
Abstract This study discusses the forecasting of 3 kg LPG gas sales at the Carica House Grocery Store. This shop as one of the LPG gas agents in the Kaliwiro area who sells 3 kg LPG Gas either retail or reseller, the number of requests for LPG gas in stores is very high , thus causing the sale of LPG gas in the shop is always uncontrolled between incoming goods and outgoing goods. Therefore, it is necessary to forecast sales. Sales forecasting has the meaning as an activity to predict product sales by using previous data as a reference in making decisions. The development of this forecasting model aims to get better forecasting results, especially regarding the accuracy of forecasting results. The Fuzzy Time Series method is used to predict the demand for 3 kg gas cylinders for the next month based on the pattern from the previous data. In data forecasting using this method, there are two forecasting techniques, namely qualitative analysis and quantitative analysis. Then for the calculation of the error value from the forecasting results, this study using MAPE produces an error value of 0,3% because it states the percentage of error results more accurately.